Perceived Corporate Glass Ceiling: A Survey Research in Bangladesh Corporate Job Sectors - Karmaker, Chhanda; Fatema, Kaniz (Asian Business Review, 2020)
The study investigated the perceived corporate glass ceiling and measured the leading factors of the glass ceiling according to gender, company types, and years of work experience. 257 adult male and female employees participated in this study as respondents, and they were from four districts of Bangladesh working in banks, multinational companies, private firms, and telecommunication sectors following a convenient sampling technique. The results revealed that 60.7% of the respondents perceived a glass ceiling exists in the workplace of Bangladesh. The researchers used mean of means analysis to compare the perceptual differences regarding the leading factors of glass ceiling according to gender, company types, and working experience and found work-life conflict as the most important factor for causing the glass ceiling.